Homer1 Scaffold Proteins Govern Ca2+ Dynamics in Normal and Reactive Astrocytes. (13th April 2016) - Buscemi, Lara; Ginet, Vanessa; Lopatar, Jan; Montana, Vedrana; Pucci, Luca; Spagnuolo, Paola; Zehnder, Tamara; Grubišić, Vladimir; Truttman, Anita; Sala, Carlo; Hirt, Lorenz; Parpura, Vladimir; et al.
Abstract: In astrocytes, the intracellular calcium (Ca 2+ ) signaling mediated by activation of metabotropic glutamate receptor 5 (mGlu5) is crucially involved in the modulation of many aspects of brain physiology, including gliotransmission. Here, we find that the mGlu5-mediated Ca 2+ signaling leading to release of glutamate is governed by mGlu5 interaction with Homer1 scaffolding proteins. We show that the long splice variants Homer1b/c are expressed in astrocytic processes, where they cluster with mGlu5 at sites displaying intense local Ca 2+ activity. We show that the structural and functional significance of the Homer1b/c–mGlu5 interaction is to relocate endoplasmic reticulum (ER) to the proximity of the plasma membrane and to optimize Ca 2+ signaling and glutamate release. We also show that in reactive astrocytes the short dominant-negative splice variant Homer1a is upregulated. Homer1a, by precluding the mGlu5-ER interaction decreases the intensity of Ca 2+ signaling thus limiting the intensity and the duration of glutamate release by astrocytes. Hindering upregulation of Homer1a with a local injection of short interfering RNA in vivo restores mGlu5-mediated Ca 2+ signaling and glutamate release and sensitizes astrocytes to apoptosis. We propose that Homer1a may represent one of the cellular mechanisms by which inflammatory astrocytic reactions are beneficial for limiting brain injury.